OP27 Dissemination and implementation in dementia care practice: a systematic scoping review. (13th September 2016) - Lourida, I; Abbott, R; Lang, I; Rogers, M; Kent, B; Thompson-Coon, J
Abstract : Background: There is a gap between the dementia care that is provided and that which research evidence suggests should be provided and this hinders efforts to improve the quality of care for people with dementia. A systematic scoping review was conducted to identify and synthesise the strategies of disseminating and implementing practices that have been shown to improve dementia care, and describe barriers and facilitators to the process. Methods: Twelve databases were searched from inception to October 2015. Backward and forward citation searching was performed and websites of relevant organisations were searched to identify unpublished material. Studies with a comparative research design (quantitative) or recognised methods of data collection (qualitative) were included if they addressed dissemination and implementation strategies or enablers and barriers to best practice across dementia stages and care settings. Titles, abstracts and full texts were screened independently by two reviewers with discrepancies resolved by a third where necessary. Data extraction was performed by one reviewer and checked by a second. The EPOC taxonomy was used to classify the implementation approaches (professional, organisational, regulatory, financial) and specific strategies used (e.g. educational meetings). A mixed-methods approach was employed to synthesise the evidence. Results: Of the 2, 609 citations retrieved, 104 met the inclusion criteria (27 quantitative, 49 qualitative and 28 mixed-methods studies). A small proportion of studies address dissemination of knowledge. Approximately 40% of studies focus on implementation strategies to improve practice in areas of dementia care ranging from use of restraints and antipsychotics to nonpharmacological behaviour management to wider culture change approaches. Most of these studies employ strategies targeting professionals (educational meetings and materials) followed by a few organisational approaches; regulatory and financial strategies are rare. Over 50% of studies address barriers, and to a lesser extent, facilitators of dementia care practices in residential care settings. Organisational factors including time constraints and increased workload are recurrent barriers, whereas leadership and managerial support are often reported to promote implementation. Ongoing analysis will provide further insight into the type and effectiveness of implementation strategies used and allow mapping of evidence gaps in this area. Discussion: The review describes the breadth of available research on dissemination and implementation strategies in dementia care and factors that may affect the translation of evidence-based research into practice. These findings will inform the development of successful implementation strategies and highlight opportunities for future research.